EURO-ASIAN COLLABORATION FOR GAMMA-RAY BURST OPTICAL OBSERVATIONS - Bogdanov, A. S.; Guziy, S. S.; Castro-Tirado, A. J.; Ugarte Postigo, A. de.; Gorosabel, J.; Jelinek, M.; Sokolov, V. V.; Fatkhullin, T. A.; Kheifets, I. M. (Одеські астрономічні публікації, 2017)
Gamma-ray burst (GRB) very interesting objects in Universe. In the study of gamma-ray burst is very important operative observations with many points in first day and other days after the burst. INTEGRAL, HETE-II and specially SWIFT era is going to leave a considerable number of detections that will allow to do important statistical analysis. We present information about Euro-Asian collaboration for GRB optical observations. To our group included researchers from: Spain, Ukraine, Russia, India, New Zealand and Czech Republic. The instruments which we using for observation have a diameter from 60cm to 6m. Optical and NIR observations are more important.